Analisis Faktor Penyebab Stres Kerja yang dialami Pekerja di Proyek Sekolah Kristen Calvin PT Total Bangun Persada Tbk. Tahun 2022 - Azizah, Firas (Journal of Public Health Education, 2024)
Introduction: Work stress is the response of the body and mind of individuals to changes in their work environment that are considered disruptive and carry potential threats to themselves. Objectives: This study aims to analyze the factors that cause work stress experienced by workers at the Calvin Christian School Project of PT Total Bangun Persada Tbk. in 2022. Method: The type of research used is a descriptive analysis method with a qualitative approach. This research was conducted on 6 informants including 2 craftsmen, 1 caster, 1 finishing worker, 1 scaffolding worker, and 1 cleaning worker. With a sampling technique using purposive sampling. Data collection uses interviews. In this research, the stages of data processing include data reduction, data presentation, and conclusion, as well as the application used by researchers, namely triangulation. Result: The results of this research show that individual factors as causes of work stress do not occur too high, because informants do not use individual factors as pressure or conflict that causes work stress when in the work environment. The work factor is the unpredictable weather so sometimes the time needed to complete the work is a little longer, but this does not make the informant feel pressured so it does not cause work stress. External factors at work do not cause high work stress, but the work environment is less comfortable for the informant because working on a clean project cannot be felt. Apart from that, supporting factors do not cause high work stress, informants always prioritize cooperation with other workers so that no informant feels difficult or has excessive burdens, apart from that, superiors also treat informants well, there is no excessive pressure, all the workers need is highly regarded by his superiors. Conclusion: Factors that cause work stress experienced by workers at the Calvin Christian School Project of PT Total Bangun Persada Tbk in 2022 include individual factors, work factors (uncertain weather), factors outside of work (the work environment is not comfortable enough), supporting factors (cooperation). However, this doesn't have a big impact as a cause of stress.